2022
DOI: 10.1111/1365-2656.13774
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence does not necessarily equal maintenance species: Avoiding biased claims of disease reservoirs when using surveillance data

Abstract: 1. Many pathogens of public health and conservation concern persist in host communities. Identifying candidate maintenance and reservoir species is therefore a central component of disease management. The term maintenance species implies that if all species but the putative maintenance species were removed, then the pathogen would still persist. In the absence of field manipulations, this statement inherently requires a causal or mechanistic model to assess.2. However, we lack a systematic understanding of (i)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Vertebrate host species integral to the persistence of JEV – whereby their absence would lead to a reduction or elimination of JEV within the community – are considered maintenance hosts. In contrast, vertebrate species that contribute to JEV transmission, but only for short periods of time or with repeated introduction are considered spillover hosts 41 . Those species which cannot infect susceptible vectors are considered dead-end hosts.…”
Section: Discussionmentioning
confidence: 99%
“…Vertebrate host species integral to the persistence of JEV – whereby their absence would lead to a reduction or elimination of JEV within the community – are considered maintenance hosts. In contrast, vertebrate species that contribute to JEV transmission, but only for short periods of time or with repeated introduction are considered spillover hosts 41 . Those species which cannot infect susceptible vectors are considered dead-end hosts.…”
Section: Discussionmentioning
confidence: 99%
“…As recently reviewed by others (e.g. [84][85][86][87][88][89][90][91][92][93][94][95]), identifying and studying reservoir hosts is not straightforward and 'target', 'source' and 'maintenance' populations may vary. Layered on top of other types of evidence, experimental challenge trials provide the strongest indication that a particular species is a confirmed reservoir host.…”
Section: (D) Virus Detection Methods and Associated Challengesmentioning
confidence: 99%
“…This can be challenging, as establishing a host infection is different from establishing host competence (Wilber et al, 2022). In addition, different levels of within-and between-species transmissions arise from an incomplete niche overlap and different contact networks (Barroso et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Determining host competence (or susceptibility) is key to determining the host range and the level to which a given pathogen is actually a true multihost generalist (Becker et al, 2020). This can be challenging, as establishing a host infection is different from establishing host competence (Wilber et al, 2022). In addition, different levels of within‐ and between‐species transmissions arise from an incomplete niche overlap and different contact networks (Barroso et al, 2023).…”
Section: Introductionmentioning
confidence: 99%